LexITA: A Quick and Reliable Assessment Tool for Italian L2 Receptive Vocabulary Size. (25th April 2020) - Amenta, Simona; Badan, Linda; Brysbaert, Marc
Abstract: In language and second language acquisition research, it is important to have a measure for tracking the proficiency level of participants. Lexical competence is fundamental for communicative purposes in a given language, and vocabulary tests are a reliable measure to assess lexical proficiency. That is why vocabulary tests have a central role in language proficiency assessment. Although many people study Italian as second language (L2), an easy-to-use vocabulary test to measure lexical proficiency is still missing. In this work, we aim to fill this gap by presenting LexITA, which is an objective, reliable, and quick assessment of Italian receptive vocabulary. LextITA was validated on students of Italian L2 and showed to be a valid measure to assess vocabulary knowledge of L2 speakers spanning different levels of proficiency.